The Influence of Self-Efficacy on Anxiety and Perfectionism among Dancers - Ananya; Smriti Sethi (International Journal of Behavioral Sciences, 2025)
The world of dance, while driven by creativity, often imposes significant psychological demands on performers. This study explored how self-efficacy influences anxiety and perfectionism—both adaptive (excellencism) and maladaptive—among dancers, with a focus on gender differences. A sample of 120 dancers (60 males, 60 females) was assessed using standardized scales. Relationships and predictive effects were assessed using statistical techniques, such as regression, Pearson correlation, and t-tests. Findings revealed no significant gender differences in overall levels of self-efficacy, anxiety, or perfectionism. However, relational patterns differed by gender. Among male dancers, self-efficacy was positively linked to both excellencism and maladaptive perfectionism, and negatively associated with anxiety. In contrast, female dancers showed a positive correlation between self-efficacy and excellencism only, with no significant link to anxiety or maladaptive perfectionism.Regression analysis further confirmed that self-efficacy significantly predicted anxiety (R² = 0.116), excellencism (R² = 0.219), and maladaptive perfectionism (R² = 0.176) in males, whereas for females, it only predicted excellencism (R² = 0.158). These findings suggest that self-efficacy acts as a psychological buffer against anxiety and maladaptive traits in male dancers, while promoting excellence in both genders. Enhancing self-efficacy could therefore support mental well-being and performance sustainability in dance training
Keywords: Anxiety; Dance; Excellencism; Perfectionism; Performance Anxiety; Self-Efficacy